Comparison of metrics to monitor and compensate for piezoceramic debonding in structural health monitoring. (March 2013) - Mulligan, Kyle R; Quaegebeur, Nicolas; Ostiguy, Pierre-Claude; Masson, Patrice; Létourneau, Sylvain
This article investigates metrics to assess and compensate for the degradation of the adhesive layer of surface-bonded piezoceramic transducers for structural health-monitoring applications. Capacitance, resonance frequency, and modal damping parameters are derived from admittance curves using a lumped parameter model to monitor the degradation of the transducer adhesive layer. A pitch-catch configuration is then used to discriminate the effect of bonding degradation on actuation and sensing. It is shown that below the first mechanical resonance frequency of the piezoceramic transducers, the degradation causes a decrease in the amplitude of the transmitted and received signals, while above resonance, in addition to a decrease in the amplitude of the transmitted and received signals, a linear phase shift is observed. A signal-correction factor is proposed to adjust signals based on adhesive degradation evaluated using the measured modal damping. The benefits of the signal-correction factor are demonstrated in the frequency domain for both the A0 and S0 modes.